2016
DOI: 10.1002/tox.22339
|View full text |Cite
|
Sign up to set email alerts
|

Bisphenol a induces autophagy and apoptosis concurrently involving the Akt/mTOR pathway in testes of pubertal SD rats

Abstract: Bisphenol A (BPA), a typical endocrine disrupting chemical (EDC), has been proven to cause male reproductive toxicity. However, the precise mechanisms of this effect are still unclear. Puberty is a crucial period of reproductive development, and adolescents are more susceptible to xenobiotics. This research was designed to explore the mechanism of BPA toxicity on pubertal male reproduction. Rats were exposed to 0, 2, 10, 50 mg kg bw BPA, then the levels of sex hormones, oxidative stress, and semen quality were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 60 publications
3
31
0
1
Order By: Relevance
“…Dans les spermatides matures, elle régule la vitalité et la mobilité des cellules [27]. Les conséquences environnementales et comportementales de l'autophagie sont de mieux en mieux comprises et ses implications sur la spermatogenèse commencent à être étudiées [41,42]. Une meilleure compréhension de la physiologie spermatique devrait permettre d'apporter des perspectives thérapeutiques pour les infertilités masculines encore étiquetées « idiopathiques » [43].…”
Section: Resultsunclassified
“…Dans les spermatides matures, elle régule la vitalité et la mobilité des cellules [27]. Les conséquences environnementales et comportementales de l'autophagie sont de mieux en mieux comprises et ses implications sur la spermatogenèse commencent à être étudiées [41,42]. Une meilleure compréhension de la physiologie spermatique devrait permettre d'apporter des perspectives thérapeutiques pour les infertilités masculines encore étiquetées « idiopathiques » [43].…”
Section: Resultsunclassified
“…Meanwhile, the phosphorylation of AMPKa and the expression of p53 might act as a contributor to the upregulation of autophagy under BPA exposure. Of note, the expression of Beclin1 is not upregulated accompany by autophagy in testis under BPA exposure [67]. With NaF exposure, the autophagy is abnormally increased as evidenced by the synchronized increase of p62, suggesting that NaF exposure impairs autophagic machinery and result in the accumulation of autophagosomes in testis [68].…”
Section: Autophagy and Testicular Homeostasismentioning
confidence: 90%
“…As recently reviewed, a growing number of environmental pollutants are now known to interfere with autophagy [96]. Non-exhaustively, cadmium [97], arsenic [98], paraquat [99], bisphenol A [100], patulin [101] and TCDD [102,103], have been shown to differentially affect autophagy. Of particular interest here, two previous studies have also reported that B[a]P can modulate both autophagy [104] and mitophagy [105].…”
Section: -3-1-autophagy: a Key Cellular Process To Cope With Stressfmentioning
confidence: 99%